Approximating data and statistical procedures. I. Approximating data - P. L. Davies (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2003)
Stochastic models approximate data and are not true representations of the same. Statistical procedure make use of approximate stochastic models to facilitate the analysis of data.
Keywords: 519; Stochastischer Prozess; Theorie